PROBLEMATIKA DALAM PELAKSANAAN PENDIDIKAN SEJARAH DI SEKOLAH MENEGAH ATAS KOTA DEPOK - Yusuf Budi Prasetya Santosa (Candrasangkala: Jurnal Pendidikan dan Sejarah, 2016)
Abstract: Educational history is an important instrument to build a nation. A proverb says that history makes people wise and sensible. Anybody could learn from history and then use the lesson for a better future. Educational history as a large concept has a smaller derivative, that is the learning of history. Historical learning is given formally from primary to secondary level of education. In the process, history teacher has a big role for the success of educational history. History teacher act as the front guard in conducting educational history. But in the process there are some problems that inhibit the success of history learning. The problem could be overcome when history teacher returns to the "rail" of true historical education.